Isolation of Fatty Acids and Other Constituents from Callicarpa macrophylla Fruits - Chung, Ill-Min; Upadhyaya, Kumud; Ahmad, Atteeque (Asian Journal of Chemistry, 2010)
Two diterpenoids, 16α-hydroxy-17-acetoxy-3-oxophyllocladane, 16α,17-dihydroxy-3-oxophyllocladane and four fatty acids, linoleic acid, stearic acid, myristic acid, octacosanoic acid along with four steroids, β-sitosterol, stigmasterol, oleanolic acid, β-sitosterol-3-O-β-Dglucoside were isolated and identified from the fruits of Callicarpa macrophylla. The structures of all compounds were elucidated by 1H NMR and 13C NMR aided by EIMS, FABMS and IR spectra and also compared with reported values.